1993
DOI: 10.1210/jcem.77.2.8102146
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine binding in a TTR Met 119 kindred.

Abstract: Recently, a transthyretin variant, TTR Met 119, in which methionine substitutes for threonine 119, a component of the protein's iodothyronine binding site, was identified in individuals with transient euthyroid hyperthyroxinemia. Healthy carriers of Met 119 have normal serum thyroid hormone concentrations, but two studies of Met 119 carriers have differed as to whether T4 binding to TTR is increased. An additional kindred has been identified by hybrid isoelectric focusing in an ongoing screening program for TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…With Thr119Met transthyretin, the thyroxine affinity was approximately doubled (K a = 3.40 ± 0.76 ¥ 10 7 l/mol; P< 0.001) with no change in immunoreactive transthyretin variant in the undiluted serum. This doubling in affinity explained the observed thyroxine levels of about 120 nmol/l in individuals with this mutation, which is identical to the value found by both Alves et al [50] and Harrison et al [51] in individuals with the Thr119Met transthyretin variant. Identical experiments carried out with Glu54Gly transthyretin showed that the thyroxine affinity of this variant was the same as for normal transthyretin.…”
Section: Further Studies On Thyroxine Bindingsupporting
confidence: 88%
See 1 more Smart Citation
“…With Thr119Met transthyretin, the thyroxine affinity was approximately doubled (K a = 3.40 ± 0.76 ¥ 10 7 l/mol; P< 0.001) with no change in immunoreactive transthyretin variant in the undiluted serum. This doubling in affinity explained the observed thyroxine levels of about 120 nmol/l in individuals with this mutation, which is identical to the value found by both Alves et al [50] and Harrison et al [51] in individuals with the Thr119Met transthyretin variant. Identical experiments carried out with Glu54Gly transthyretin showed that the thyroxine affinity of this variant was the same as for normal transthyretin.…”
Section: Further Studies On Thyroxine Bindingsupporting
confidence: 88%
“…However, in a later, slightly higher resolution X-ray study, Hamilton et al [49] showed that residue 6 was not involved in thyroxine binding. In 1993, a group of researchers lead by Pedro Costa and Maria Saraiva identified individuals who had the transthyretin variant Thr119Met, which was associated with transient euthyroid hyperthyroxinemia [50]. In addition, they found an individual who was heterozygous for the double mutation Thr119Met and His90Asn.…”
Section: Further Studies On Thyroxine Bindingmentioning
confidence: 99%
“…In opposition, TTR T119M is a non-pathogenic variant. This is a particularly interesting variant since it has been described in heterozygotic carriers and also in compound heterozygotic carriers of both TTR V30M and TTR T119M [25]. Curiously in the last case the TTR T119M variant seems to have a protective role over the effect of TTR V30M since these compound heterozygotes present a more benign form of the disease [26,27,28].…”
Section: Ttr Variantsmentioning
confidence: 99%
“…TTR L55P, a variant with a substitution of a proline for leucine, is highly amyloidogenic and is associated with the most aggressive form of the disease [3]. Likewise, TTR Y78F is a very aggregate-prone mutant, namely under physiological conditions [4], while TTR T119M, with a substitution of methionine for threonine, is a non-amyloidogenic and non-pathogenic TTR variant with protective properties [5].…”
Section: Introductionmentioning
confidence: 99%